Estimation and Analysis with a WDI Production Function - Göran Eriksson; Ulf Jakobsson; Leif Jansson (The Research Institute of Industrial Economics (IUI), 1976)
By means of a new type of production function - the WDI function an examination has been made of the production structure in thirteen branches of Swedish manufacturing industry. The function used which is the same in all thirteen branches, allows for variable elasticity of substitution and gives us a possibility of distinguishing different types of bias 1n technological development. It was found for instance that the hypothesis on Hicks neutrality can be dismissed for most branches. The data material used contains both production data (i.e. observations regarding capital, labour and production) and observations of the factor income shares. A 'Full Information Maximum Likelihood (FIML)' method was used for estimation.
Keywords: L11; L60; 330; Manufacturing; Production structure